Espionage and Counterintelligence in Occupied Persia (Iran) - O'Sullivan, Adrian. author. aut Link
XXVIII, 293 p.
Keywords: The sequel to Nazi Secret Warfare , which portrayed the catastrophic failure of Germany's clandestine services in Persia (Iran) during the Second World War. By contrast but based on equally solid archival evidence, this companion volume tells the other side of the same fascinating story, introducing us to spies, spycatchers, and spymasters.